The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/vnl.21821
|View full text |Cite
|
Sign up to set email alerts
|

Application of graphene‐based adsorbents in the treatment of dye‐contaminated wastewater; kinetic and isotherm studies

Abstract: The adsorption of methylene blue (MB) on graphene‐based adsorbents was tested through the batch experimental method. Two types of graphene‐based adsorbents as graphene oxide (GO) and reduced graphene oxide (RGO) were compared to investigate the best adsorbent for MB removal. So that optimizing the MB removal for the selected type of graphene‐based adsorbent, the diverse experimental factors, as pH (2–10), contact time (0–1440 min), adsorbent dosage (0.5–2 g/L), and initial MB concentration (25–400 mg/L) were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
(60 reference statements)
1
8
0
Order By: Relevance
“…Compared with CC-SFS, CC-SFS-MB has many new peaks, such as 1605, 1393, and 1348 cm À1 , which correspond to C═C, S═O, and C═N vibrations. [34] These FTIR results confirmed that the MB molecules have been grafted on the CC-SFS successfully.…”
Section: Characterization Of Adsorbentsupporting
confidence: 57%
“…Compared with CC-SFS, CC-SFS-MB has many new peaks, such as 1605, 1393, and 1348 cm À1 , which correspond to C═C, S═O, and C═N vibrations. [34] These FTIR results confirmed that the MB molecules have been grafted on the CC-SFS successfully.…”
Section: Characterization Of Adsorbentsupporting
confidence: 57%
“…A typical diffraction peak at 2θ around 10.02 indicated that graphene has transformed into a compound due to oxygen-containing functional groups. [23,24] We selected Truesoft™ because it is a widely used acrylate-based dental relining material. Incorporating low weight fraction of GO nanosheets enhanced the physical properties of RDL without negatively affecting the surface roughness and the wettability properties possibly confirm our hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…A typical diffraction peak at 2 θ around 10.02° indicated that graphene has transformed into a compound due to oxygen‐containing functional groups. [ 23,24 ]…”
Section: Discussionmentioning
confidence: 99%
“…Methylene blue (MB) dye [25] shell charcoal (GNC) and Eichhornia charcoal (EC). The results showed that CR adsorption on GNC and EC followed a second request motor model.…”
Section: Mediummentioning
confidence: 99%